Butanol Production from Halophyte Seepweed Suaeda salsa by Simultaneous Saccharification and Fermentation - Zhao, Shi-Hao; Ma, Tong-Suo; Zhang, Hong-Bing (Asian Journal of Chemistry, 2011)
In this study, the halophyte seepweed Suaeda salsa was used for butanol production by simultaneous saccharification and fermentation. The main nutrients of S. salsa was estimated at first and then the influence of different factors in simultaneous saccharification and fermentation, such as substrate concentration, cellulase dosages and CaCO3 were investigated and optimized by the one-factor-at-a-time approach and further optimized by response surface methodology. The optimal conditions for butanol production by simultaneous saccharification and fermentation were: seepweed 34.5 g (0.8-1.0 mm in length, pretreated by 4 % NaOH), mixed with cellulase 23.7 FPIU/g seepweed and nutrition solution (yeast extract 1.0 g/L, KH2PO4 0.5 g/L, K2HPO4 0.5 g/L, CaCO3 4.8 g/L, ammonium acetate 2.2 g/L, p-aminobenzoic acid 0.001 g/L, vitamin B1 0.001 g/L, biotin 0.00001 g/L, MgSO4·7H2O 0.2 g/L, MnSO4·7H2O 0.01g/L, NaCl 0.01 g/L, FeSO4·7H2O 0.01g/L. Inoculum volume of 10 % (v/v) and the medium volume was 50/250 mL flask, under these conditions, the butanol yield could reach 3.5 g/L after 72 h fermentation.